A new shell-beam element modeling method and its use in crash simulation of triaxial braided composites. (15th January 2017) - Shi, Danghe; Xiao, Xinran
Abstract: To overcome the instability encountered in axial crash simulations of composite tubes with shell elements, a new modeling technique: the shell-beam (SB) element method, has been developed. This method creates an element which is capable of deforming in the through thickness direction while retaining the efficiency of the shell elements. The SB element was evaluated with virtual one-element, cantilever beam and in-plane compression tests. The results showed that the SB element is effective in terms of overcoming the instability and convergence issues of traditional 2D and 3D discretized elements under in-plane compression. The SB element was further evaluated together with an in-house material model, called the enhanced continuum damage mechanics (ECDM) model, in crash simulations of triaxial braided composite tubes with five configurations and seven test conditions. The simulations captured both the failure morphologies and force-displacement responses obtained in experiments.